Rethinking Motivation and Reward Management: What We Know and Do not Know - Wang, Zheni (Edward Elgar Publishing Ltd., 2025)
This innovative book examines the controversial relationship between motivation and rewards from multiple theoretical and practical perspectives. It analyzes cutting-edge research on work motivation and reward management's economic and psychological roots and identifies future directions for advancement in the field. © Zheni Wang 2025.
Keywords: Compensation And Benefits; Motivation At Work; Reward Management; Self-Regulations; Total Rewards; Work Engagement; dept.mgt